STRATEGI PROMOSI KESEHATAN BERBASIS KEARIFAN LOKAL TERHADAP PERUBAHAN PERILAKU KESEHATAN MASYARAKAT: LITERATUR REVIEW - Syamsuriah Syamsuriah; Sakinah Amir (Yayasan Nusantara Hasana Berdikari, 2026)
Prevention and control of hypertension are major challenges in public health management, especially in areas with limited resources. Community-based interventions are an effective strategy that can improve public awareness and behavior related to hypertension. This literature review aims to evaluate hypertension prevention and control behaviors through community-based interventions as a strategy. This study used a literature review method by examining 9 journals obtained from reputable databases such as PubMed, Science Direct, and Proquest, published between 2022 and 2025. The analysis of these 9 articles indicates that community-based interventions involve intervention approaches based on behavioral theory models, interventions that emphasize increasing community-based health literacy and utilizing technology, and analysis of behavioral determinants, lifestyle, and systemic barriers that influence hypertension prevention and control practices. Therefore, hypertension prevention and control behaviors through community-based interventions are an effective strategy to minimize negative health impacts.